SPECIFIC PROPERTIES OF SURFACTANTS AND THEIR CLASSIFICATION (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article describes the importance and development of surfactants. About their use and relevance in today's marriage. There was also talk about their properties.